Slurry composition for lightweight aerated concrete, and method for producing the slurry composition for lightweight aerated concrete
Patent Information
- Application Number
- JP2025059178
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本開示によれば、貯蔵安定性を保ちつつ、かつ沈降後も優れた流動性を有する軽量気泡コンクリート用スラリー組成物を提供すること、及び、上記スラリー組成物の製造方法を提供することができる。
Smart Images

Figure 2026166313000001 
Figure 2026166313000002 
Figure 2026166313000003
Abstract
Description
Technical Field
[0001] The present disclosure relates to a slurry composition for lightweight cellular concrete, and a method for producing the slurry composition for lightweight cellular concrete.
Background Art
[0002] Autoclaved Lightweight Aerated Concrete (hereinafter referred to as "ALC") has many advantages such as being lighter than ordinary concrete, and at the same time having excellent fire resistance, heat insulation properties, and workability, so it is widely used as a panel-shaped building material for exterior wall materials, floor materials, roof materials, interior wall materials and the like of buildings.
[0003] Due to the properties of ALC, a foaming agent is mixed in the production process. Examples of the foaming agent include a slurry composition produced by mixing aluminum powder and water. This slurry composition has the property of generating hydrogen gas when aluminum powder reacts under alkaline conditions, and is used for foaming of inorganic foams such as ALC, foaming type filling grout materials, and foaming type porous ceramics, and for hydrogen production applications (see, for example, Patent Document 1, Patent Document 2, and Patent Document 3).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Patent Document 3
Patent Document 4
Summary of Invention
Problems to be Solved by the Invention
[0005] In using a slurry composition for producing ALC, steps of preparing and storing the slurry composition before molding ALC, and a step of causing the prepared slurry composition to flow through a pipe or the like are required. Conventionally, in these steps, the storage stability of the slurry composition is insufficient due to the slurry composition remaining in a tank or a pipe for a long period of time, which has caused a problem that aluminum powder reacts before being used for the intended application. Further, there has been a problem that the aluminum powder in the slurry composition settles and accumulates in a dead space where fluid easily remains, such as around a valve present in a tank or a pipe, and the poor fluidity of the deposit causes clogging of equipment.
[0006] The present disclosure aims to provide a slurry composition for ALC that has improved storage stability and has excellent fluidity even after sedimentation, and to provide a method for producing the slurry composition. [Means for Solving the Problems]
[0007] Examples of embodiments of the present disclosure are listed below. [1] A slurry composition for producing lightweight aerated concrete, the slurry composition comprising: aluminum powder, an acid compound having a pKa in a range of 2.0 or more and 4.0 or less, and water, wherein the slurry composition has a zeta potential of -32 mV or more and +32 mV or less. [2] The slurry composition according to item 1, wherein a specific volume of a deposited layer of the slurry composition obtained by a centrifugal sedimentation method is in a range of 2.7 mL / g or more and 7.0 mL / g or less. [3] The ratio of the addition amount [g ac / g Al of the acid compound to 1 g of the aluminum powder to the specific surface area [cm 2 Al / g Al of the aluminum powder (the addition amount of the acid compound / the specific surface area) is 2×10-7 [g P / cm 2 Al or more, the slurry composition according to item 1 or 2. [4] The slurry composition according to any one of items 1 to 3, wherein the acid compound contains phosphoric acid. [5] The slurry composition according to any one of items 1 to 4, comprising 800 parts by mass or more and 1200 parts by mass or less of the water with respect to 100 parts by mass of the aluminum powder. [6] The slurry composition according to any one of items 1 to 5, wherein the 50% cumulative average particle diameter (D50) in terms of volume of the aluminum powder is in the range of 15 μm or more and 55 μm or less. [7] The slurry composition according to any one of items 1 to 6, wherein the pH of the acid compound aqueous solution, which is a mixture of the acid compound and the water, is in the range of 2.0 or more and 4.5 or less. [8] The slurry composition according to any one of items 1 to 7, wherein the surface of the aluminum powder has hydrophilicity. [9] A method for producing a slurry composition for producing lightweight cellular concrete, the production method comprising: mixing aluminum powder, an acid compound having a pKa in the range of 2.0 or more and 4.0 or less, and water. The zeta potential of the slurry composition is -32 mV or more and +32 mV or less.
[10] The production method according to item 9, wherein the specific volume of the deposited layer of the slurry composition obtained by a centrifugal sedimentation method is 2.7 mL / g or more and 7.0 mL / g or less.
[11] The addition amount [g of the acid compound per 1 g of the aluminum powder ac / g Al and the specific surface area [cm of the aluminum powder 2 Al / g AlThe ratio (amount of the acid compound added / specific surface area) is 2 × 10 -7 [g P / cm 2 Al The manufacturing method described in item 9 or 10, which is greater than or equal to the above.
[12] The method for producing the product according to any one of items 9 to 11, wherein the acid compound contains phosphoric acid.
[13] A manufacturing method according to any one of items 9 to 12, wherein the amount of water is 800 parts by mass or more and 1200 parts by mass or less per 100 parts by mass of the aluminum powder.
[14] The manufacturing method according to any one of items 9 to 13, wherein the 50% cumulative average particle size (D50) of the aluminum powder on a volume basis is 15 μm or more and 55 μm or less.
[15] The manufacturing method according to any one of items 9 to 14, wherein the pH of the aqueous solution of the acid compound, which is a mixture of the acid compound and the water, is in the range of 2.0 to 4.5.
[16] A manufacturing method according to any one of items 9 to 15, comprising the step of applying a hydrophilic treatment to the surface of the aluminum powder. [Effects of the Invention]
[0008] This disclosure provides a slurry composition for lightweight aerated concrete that maintains storage stability and has excellent fluidity even after settling, and also provides a method for producing the slurry composition. [Modes for carrying out the invention]
[0009] Examples of embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments. The upper and lower limits in each numerical range of the following embodiments can be arbitrarily combined to form any numerical range.
[0010] Slurry composition for lightweight aerated concrete The slurry composition of this disclosure is a slurry composition for the manufacture of lightweight aerated concrete, and the slurry composition contains aluminum powder, an acid compound having an acid dissociation constant (hereinafter also referred to as pKa) in the range of 2.0 to 4.0, and water, and has a zeta potential of -32mV to +32mV. With this configuration, it is possible to exhibit excellent storage stability as a foaming agent for inorganic foams and to make the fluidity of the slurry composition deposit excellent. The reason for this is not limited to theory, but is thought to be as follows. In general, the settling patterns of aluminum particles can be classified into the following three types according to the aggregation form: interference settling, in which aluminum particles are evenly dispersed in water and deposited in a stacking manner; phase settling, in which aluminum particles settle while creating a gradation with aggregation; and consolidation settling, in which aluminum particles aggregate in a cross-linking manner and settle as a group. Because the zeta potential is in the above value range, cross-linking aggregation of aluminum powders is easily obtained when the slurry composition is retained, which contributes to the consolidation settling of the slurry composition. Compared to slurry compositions that settle and deposit densely, such as interference sedimentation and phase-solidification types, slurry compositions in this state exhibit higher fluidity of the deposits, thus suppressing clogging of equipment. Furthermore, because the pKa of the acid compound is within the above range, it effectively adjusts the pH of the slurry composition, controlling the reaction between aluminum powder and water and contributing to excellent storage stability. Moreover, the acid compound covers the surface of the aluminum powder, forming a film that suppresses the reaction between aluminum powder and water before use in the intended application, contributing to improved storage stability. Thus, by using an acid compound with a pKa within the above range in a slurry containing aluminum powder and water (hereinafter also referred to as "aluminum slurry"), it is possible to control the reaction between aluminum powder and water while adjusting the zeta potential to a range of -32mV to +32mV, thereby achieving both excellent storage stability and suppression of clogging.
[0011] The lower limit of the zeta potential is preferably -28mV or higher, -25mV or higher, or -22mV or higher. The upper limit of the zeta potential that can be arbitrarily combined with these lower limits is more preferably +30mV or lower, +28mV or lower, or +25mV or lower. When the zeta potential is within the above range, the fluidity of the slurry composition is further improved.
[0012] The slurry composition of this disclosure preferably has a specific volume of the sediment layer obtained by centrifugal sedimentation of 2.7 mL / g or more, 3.5 mL / g or more, or 4.0 mL / g or more. The upper limit of the specific volume of the sediment layer, which can be arbitrarily combined with these lower limits, is more preferably 7.0 mL / g or less, 6.5 mL / g or less, or 6.0 mL / g or less. The fluidity of the slurry composition is further improved when the specific volume of the sediment layer is within the above range.
[0013] <Aluminum powder> The slurry composition contains aluminum powder. The aluminum powder is a powder containing particulate aluminum and has the function of reacting with water under alkaline conditions to produce hydrogen gas, as shown in formula (1) below. Due to this function, bubbles can be formed within the ALC during ALC molding. 2Al + 2OH - +2H2O→2AlO2 - +3H2(1)
[0014] The above-mentioned aluminum powder can be given good water dispersibility by having hydrophilicity on its surface. While not limited to the following, various methods can be selected for hydrophilic treatment of aluminum powder, such as a method in which aluminum powder that has been dry-ground with fatty acids as a grinding aid is heat-treated to remove fatty acids that inhibit water dispersibility, or a method in which a surfactant is added to aluminum powder produced by a wet grinding method in which fatty acids or their derivatives are produced in a hydrocarbon solvent as a grinding aid. The hydrophilicity of the aluminum powder surface can be confirmed by measuring the contact angle of the aluminum powder. The above contact angle is a value calculated using the pressure rise value when a liquid is permeated into the powder, and is calculated using the method shown in Patent Document 4. Specifically, the method involves "filling a cell having liquid-permeable ends with powder, and..." The steps include sealing the end of the cell filled with the powder that is free to pass liquid and the end opposite to the end that is free to pass liquid, The steps include bringing liquid into contact with the liquid-permeable end of the cell, The steps include measuring the pressure inside the cell generated by vertically permeating the powder layer filled inside the cell with the liquid, A step of calculating the contact angle between the liquid and the powder surface from the pressure inside the cell, A contact angle measurement method comprising [equipment name]. The contact angle of the aluminum powder of this disclosure is preferably 65° or more and 110° or less, more preferably 70° or more and 100° or less, and even more preferably 75° or more and 90° or less.
[0015] Various methods can be selected for the production of aluminum powder, including conventional ball mills or grinding methods such as media-agitated mills (wet or dry grinding methods). In particular, when using dry ball mill grinding in a nitrogen atmosphere or wet ball mill grinding in a hydrocarbon solvent, it is preferable to include a grinding aid from the viewpoint of improving grinding efficiency. The grinding aid is not limited to the following, but higher saturated fatty acids such as stearic acid and palmitic acid, and higher unsaturated fatty acids such as oleic acid can be used. In the wet grinding method, examples of hydrocarbon solvents include aliphatic hydrocarbons such as mineral spirits, solvent naphtha, LAWS (Low Aromatic White Spirit), HAWS (High Aromatic White Spirit), or aromatic hydrocarbons such as toluene, and one or more selected from these can be used in combination. It is also possible to mix the aluminum powder with organic matter containing the above-mentioned hydrocarbon solvent and process it into a paste to use as aluminum paste.
[0016] The aluminum powder may have organic matter containing surfactants such as nonionic surfactants, cationic surfactants, or anionic surfactants on its surface. This allows the aluminum powder to acquire good hydrophilicity and improves its dispersibility in water, thus enabling more favorable mixing of the aluminum powder and water.
[0017] The aluminum powder may have an additional coating on its surface, such as aluminum hydroxide or aluminum oxide. This can further improve the storage stability of the aluminum powder.
[0018] The 50% cumulative average particle size (D50) of the aluminum powder, calculated by volume, is preferably in the range of 15 μm or more and 55 μm or less. More preferably, it is 20 μm or more and 45 μm or less, and even more preferably, 23 μm or more and 40 μm or less. By having the 50% cumulative average particle size (D50) calculated by volume within the above range, the foaming rate and foaming efficiency can be more effectively controlled. The method for calculating the 50% cumulative average particle size (D50) calculated by volume will be described in the examples below.
[0019] The aluminum powder content in the slurry composition is preferably 3.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 8.0% by mass or more, based on the total mass of the slurry composition. This allows for efficient generation of hydrogen gas and makes it suitable for use as a blowing agent for inorganic foams and for hydrogen production applications. However, to maintain the water dispersibility of the aluminum powder, the content is 20% by mass or less.
[0020] <water> The slurry composition of this disclosure contains water. The water primarily serves to impart fluidity to the slurry composition and functions as a dispersion medium for the aluminum powder. The water is not limited to the following, but can be used, for example, well water, industrial water containing impurities, RO water, distilled water, or deionized water. The water content in the slurry composition is preferably 800 parts by mass or more and 1200 parts by mass or less per 100 parts by mass of aluminum powder. This improves the dispersion stability of the aluminum powder in the slurry composition and improves the fluidity of the slurry composition. Furthermore, it allows for a suitable volume of the slurry composition from the viewpoint of saving space in storage tanks, etc.
[0021] The lower limit of the water content in the slurry composition is not particularly limited, but is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, based on the total mass of the slurry composition. The upper limit of the water content in the slurry composition is not particularly limited, but is preferably 95% by mass, more preferably 93% by mass, and even more preferably 92% by mass.
[0022] When the water content in the slurry composition is 80% by mass or more, the dispersion stability of the aluminum powder in the slurry composition is improved, viscosity is reduced, and sediment is decreased, resulting in sufficiently excellent fluidity of the slurry composition and its sediment. Furthermore, when the water content is 95% by mass or less, the volume of the slurry composition can be made suitable from the viewpoint of saving space in the stirring and mixing process and storage tanks, and pH adjustment can be easily performed when used as a foaming agent, resulting in appropriate foaming efficiency.
[0023] <Acid compound> The slurry composition of this disclosure contains an acid compound having a pKa in the range of 2.0 to 4.0. Preferably, the pKa is between 2.1 and 3.5, and more preferably between 2.15 and 3.15. The acid compound may also contain an acid compound having a pH buffering effect. By containing the acid compound in the slurry composition, the pH of the slurry composition can be adjusted to a suitable range, thereby improving storage stability. Furthermore, by suitably coating the surface of the aluminum powder with anions of the acid compound, the zeta potential can be adjusted to an appropriate range, thereby improving the fluidity of the deposits in the slurry composition. Note that the pKa of the acid compound can be a generally known value.
[0024] In this disclosure, the acid compound is preferably an aqueous solution of the acid compound, which is a mixture with the water. The pH of the aqueous solution of the acid compound is preferably in the range of 2.0 to 4.5. More preferably 2.1 or higher, 2.2 or higher, or 2.3 or higher. The upper limit of pH that can be optionally combined with these lower limits is more preferably 4.5 or lower, 4.0 or lower, or 3.5 or lower. By keeping the pH within the above range, it is possible to prevent the pH of the slurry composition from becoming extremely alkaline or acidic, suppress the reaction of the aluminum powder, and improve storage stability.
[0025] The preferred amount of acid compound to add to the above aluminum powder is the amount of acid compound added per 1 g of aluminum powder [gac / g Al ] and the specific surface area of the above aluminum powder [cm² 2 Al / g Al It is expressed as a ratio of (amount of the above acid compound added / above specific surface area), and is 2 × 10 -7 [g ac / cm 2 Al The ratio (amount of the above acid compound added / above specific surface area) is more preferably 3 × 10 -7 [g P / cm 2 Al ] or more, and more preferably 5 × 10 -7 [g P / cm 2 Al ] or more, and particularly preferably 7 × 10 -7 [g P / cm 2 Al The ratio (amount of the above acid compound added / above specific surface area) is set to 5 × 10 in order to appropriately adjust the water dispersibility and reactivity of the aluminum powder with water. -5 [g P / cm 2 Al The value may be less than or equal to the above. By adjusting the amount of acid compound added within the above range, the pH of the slurry composition can be adjusted to a suitable range, thereby improving storage stability. In addition, the ions of the acid compound suitably cover the surface of the aluminum powder, allowing the zeta potential to be adjusted to an appropriate range, thereby improving the fluidity of the deposits in the slurry composition. Note that the specific surface area of the above aluminum powder is [cm²]. 2 Al / g Al The measurement of [ ] will be described later in the examples.
[0026] In this disclosure, the above acid compound preferably contains at least one selected from the group consisting of phosphoric acid compounds, citrate compounds, and carbonate compounds, and more preferably the above acid compound contains a phosphoric acid compound. The content of the phosphoric acid compound in the slurry composition relative to water is preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, and more preferably 0.3 parts by mass or less, per 100 parts by mass of water. This prevents a significant decrease in the pH of the slurry composition due to the addition of excessive phosphoric acid, and makes the pH of the slurry composition more suitable. The content of phosphoric acid relative to water in the slurry composition is 0.01 parts by mass or more.
[0027] Any phosphate compound that can supply phosphate ions can be suitably used. Examples of phosphate compounds include orthophosphates and phosphate salts, and examples of phosphate salts include monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monosodium phosphate, disodium phosphate, trisodium phosphate, monoammonium phosphate, and diammonium phosphate.
[0028] The phosphoric acid compound is preferably added in liquid form, for example, in the form of an aqueous solution. This allows for adjustment of the viscosity of the phosphoric acid to an appropriate range, thereby improving the handling of the phosphoric acid during the production of the slurry composition and making the workability more favorable. The concentration of the aqueous phosphoric acid solution is preferably 75% by mass or more, and more preferably 85% by mass or more. This further enhances the aforementioned effects and allows for an appropriate storage volume.
[0029] Method for producing slurry composition for lightweight aerated concrete This disclosure provides a method for producing a slurry composition for manufacturing lightweight aerated concrete. The above manufacturing method is Aluminum powder and Acid compounds having a pKa in the range of 2.0 or higher and 4.0 or lower, The process involves mixing water with [a certain substance]. The zeta potential of the slurry composition is in the range of -32mV to +32mV. Preferred embodiments of the slurry composition are as described in the section on "Slurry Composition for Lightweight Aerated Concrete" above. [Examples]
[0030] The following describes examples and comparative examples of embodiments of this disclosure, but this disclosure is not limited to the following examples and comparative examples.
[0031] Measurement and Evaluation Methods <Cumulative average particle size (D50) of aluminum powder [μm]> The cumulative average particle size (D50) of aluminum powder was calculated from the cumulative distribution curve obtained by measuring the volume-based particle size distribution in water using laser diffraction and scattering. More specifically, the particle size D50 (median diameter) at which the cumulative value from the smallest diameter side in the cumulative distribution curve reaches 50% was treated as the cumulative average particle size (D50). The MT3300 series from Microtrac-Bell was used to measure the particle size distribution using laser diffraction and scattering.
[0032] <Specific surface area of aluminum powder [cm²] 2 Al / g Al ]〉 In this disclosure, the specific surface area [cm²] of aluminum powder 2 Al / g Al The specific surface area [m²] of the aluminum powder was calculated as follows: For the slurry composition, measurements were performed using the laser diffraction-scattering method, and the analysis was performed assuming that all particles were spherical. 2 Al / mL Al The specific surface area of the obtained aluminum particles [m²] was obtained. 2 Al / mL Al By dividing ] by the density of the aluminum powder, the specific surface area [cm²] on a mass basis of the particles can be obtained. 2 Al / g Al ] was obtained.
[0033] <Specific volume of sedimentary layer [mL / g]> In this disclosure, the specific volume of the sediment in the slurry composition was calculated as follows. The slurry composition was subjected to centrifugal sedimentation using a centrifugal sedimentation type dispersion stability evaluation device (LUMiSizer611 (manufactured by LUM GmbH, Germany)) (measurement cell: 2 mm made of polyamide, sample volume: approximately 0.4 mL, temperature: 25°C, rotation speed: 250 rpm, processing time: 50 minutes). After that, the volume [mL] of the sediment layer was measured by measuring the X-ray transmission profile (measurement time: 30 seconds (interval of 3 seconds x 10 times)) using a LUMiReader X-RAY. The obtained volume [mL] of the sediment layer was divided by the content [g] of aluminum powder in the sample used for measurement to obtain the specific volume [mL / g] of the sediment layer.
[0034] <Zeta potential [mV]> In this disclosure, the zeta potential was measured using a flow potential measuring device (Stabino, manufactured by Microtrac) based on the flow potential method.
[0035] <Residual rate [%]> In this disclosure, the residue rate was calculated as follows: 100 mL of the slurry composition to be evaluated was added to a 100 mL graduated cylinder, and after standing for 80 minutes, the amount of sediment [mL] accumulated in the graduated cylinder was visually measured. Then, the graduated cylinder was tilted 180° for 30 seconds to remove the supernatant of the slurry composition, and the amount of residual sediment [mL] that remained unremoved was visually measured. The residue rate was calculated from the obtained amount of sediment [mL] and residual amount [mL] according to the following formula (2). Residual rate [%] = Residual amount [mL] / Sediment volume [mL] (2)
[0036] <Storage Stability> In this disclosure, storage stability was evaluated as follows: 110 g of the slurry composition to be evaluated was placed in a 200 mL Erlenmeyer flask and left to stand for 48 hours at room temperature (20°C) and 60% humidity. The cumulative amount of hydrogen gas generated was measured. The amount of hydrogen gas generated during the standing period was evaluated as follows, and this was used as an indicator of the storage stability of the slurry composition. ○: Less than 10 mL in 48 hours △: Less than 10 mL in 24 hours, 10 mL or more in 48 hours ×: More than 10 mL in 24 hours
[0037] Examples and Comparative Examples <Examples 1-27, Comparative Examples 1-15> An aqueous solution of the acid compound was prepared by mixing an acid compound with water. Aluminum powder was dispersed in the aqueous solution of the acid compound, and the mixture was stirred for 1 hour to prepare a slurry composition. The conditions of the slurry composition and the results obtained are shown in the table below.
[0038] [Table 1]
[0039] [Table 2]
[0040] [Table 3] [Industrial applicability]
[0041] The slurry composition provided in this disclosure is suitably used in the production of lightweight cellular concrete that maintains storage stability and excellent fluidity even after settling. It can also be suitably used in hydrogen production applications.
Claims
1. A slurry composition for producing lightweight aerated concrete, wherein the slurry composition is Aluminum powder and Acid compounds with a pKa in the range of 2.0 or higher and 4.0 or lower, It contains water, A slurry composition having a zeta potential of -32 mV or higher and +32 mV or lower.
2. The slurry composition according to claim 1, wherein the specific volume of the deposited layer of the slurry composition obtained by centrifugal sedimentation is in the range of 2.7 mL / g or more and 7.0 mL / g or less.
3. The addition amount [g of the acid compound relative to 1 g of the aluminum powder ac / g Al and the specific surface area [cm of the aluminum powder 2 Al / g Al (the addition amount of the acid compound / the specific surface area) is 2 × 10 -7 [g ac / cm 2 Al or more, the slurry composition according to claim 1 or 2.
4. The slurry composition according to claim 1 or 2, wherein the acid compound contains phosphoric acid.
5. The slurry composition according to claim 1 or 2, comprising 800 to 1200 parts by mass of water per 100 parts by mass of the aluminum powder.
6. The slurry composition according to claim 1 or 2, wherein the 50% cumulative average particle size (D50) of the aluminum powder, calculated by volume, is in the range of 15 μm or more and 55 μm or less.
7. The slurry composition according to claim 1 or 2, wherein the pH of the aqueous solution of the acid compound, which is a mixture of the acid compound and the water, is in the range of 2.0 to 4.
5.
8. The slurry composition according to claim 1 or 2, wherein the surface of the aluminum powder is hydrophilic.
9. A method for producing a slurry composition for manufacturing lightweight aerated concrete, wherein the manufacturing method is: Aluminum powder and Acid compounds with a pKa in the range of 2.0 or higher and 4.0 or lower, The process involves mixing water with [a certain substance]. A method for producing the slurry composition wherein the zeta potential of the slurry composition is between -32 mV and +32 mV.
10. The manufacturing method according to claim 9, wherein the specific volume of the deposited layer of the slurry composition obtained by centrifugal sedimentation is 2.7 mL / g or more and 7.0 mL / g or less.
11. Amount of the acid compound added to 1 g of the aluminum powder [g] ac / g Al ] and the specific surface area of the aluminum powder [cm² 2 Al / g Al The ratio (amount of the acid compound added / specific surface area) is 2 × 10 -7 [g ac / cm 2 Al The manufacturing method according to claim 9 or 10, which is as described above.
12. The method for producing the product according to claim 9 or 10, wherein the acid compound contains phosphoric acid.
13. The manufacturing method according to claim 9 or 10, wherein the amount of water is 800 parts by mass or more and 1200 parts by mass or less per 100 parts by mass of aluminum powder.
14. The manufacturing method according to claim 9 or 10, wherein the 50% cumulative average particle size (D50) of the aluminum powder on a volume basis is 15 μm or more and 55 μm or less.
15. The manufacturing method according to claim 9 or 10, wherein the pH of the aqueous solution of the acid compound, which is a mixture of the acid compound and the water, is in the range of 2.0 to 4.
5.
16. The manufacturing method according to claim 9 or 10, further comprising the step of applying a hydrophilic treatment to the surface of the aluminum powder.
Citation Information
Patent Citations
Mullite based foaming type porous ceramics and its production
JP1993238846A
Manufacturing method of grout filler material of post-foaming type
JP2015189634A
Method for producing water-repellent lightweight foam concrete
JP2016056069A
Contact angle measurement method, contact angle measurement device, and powder charging device
JP2019144130A